THE EFFECT OF PRODUCT VARIATIONS AND CUSTOMER VALUES ON CUSTOMER SATISFACTION HANNAH CATALOG BANDAR LAMPUNG - Ardansyah; Muhammad Haykal Marlyn (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to evaluate the impact of variables such as customer value and product variety on consumer satisfaction from Hannah Catalog. The population that was the focus of the study consisted of 100 customers who used the sampling technique using purposive sampling. The analysis method used is multiple linear regression. The purpose of this research is to help Hannah Catalog increase customer value and product variety in order to better meet customer satisfaction, which can increase competitiveness. This research is expected to provide guidance to Hannah Catalog to improve customer satisfaction levels with their products. The results of the study show that product variety and customer value each have a positive and significant effect on customer satisfaction. Simultaneously, both variables also have a significant effect on customer satisfaction. A coefficient of determination value (R²) of 0.575 indicates that product variation and customer value can explain 57.5% variation in customer satisfaction. These findings provide important implications for Hannah Catalog's management in designing strategies for improving product quality and creating customer value.